2013
DOI: 10.5588/ijtld.12.0665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on patient-reported outcomes in sarcoidosis

Abstract: Sarcoidosis significantly reduces patients' health status, both independently and also due to increased BMI. Reduction in BMI may contribute to improved spirometry results and health status of patients with sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 18 publications
0
22
0
5
Order By: Relevance
“…In that clinical study of 184 Serbian patients with sarcoidosis and age-and sex-matched control subjects, higher BMI was associated with lower FVC %, higher fatigue, and poorer self-reported health status. 30 Although the BWHS lacks detailed immunologic and clinical data, we observed a positive association between BMI at baseline and the number of participants with sarcoidosis reporting two or more symptoms at diagnosis.…”
Section: Discussionmentioning
confidence: 57%
“…In that clinical study of 184 Serbian patients with sarcoidosis and age-and sex-matched control subjects, higher BMI was associated with lower FVC %, higher fatigue, and poorer self-reported health status. 30 Although the BWHS lacks detailed immunologic and clinical data, we observed a positive association between BMI at baseline and the number of participants with sarcoidosis reporting two or more symptoms at diagnosis.…”
Section: Discussionmentioning
confidence: 57%
“…A meta-analysis designed to assess the impact of obesity on outcomes in RA demonstrated that obese patients had significantly worse Health Assessment Questionnaire scores and higher pain scores at follow-up relative to non-obese patients, even after controlling for relevant covariates (15). Similarly, studies evaluating the relationship between obesity and PROs in patients with sarcoidosis or axial spondyloarthritis have demonstrated an independent association between the presence of obesity and worse PROs, including pain, fatigue, and indices of global health status (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown the impact of sociodemographic factors such as poverty on PROs, but again, much of the variation in PROs remains unexplained (14). Previous studies of other inflammatory conditions have shown an association between excess adiposity and worse PROs (15)(16)(17), but prior research designed to understand the contribution of obesity to PROs in SLE is scant and conflicting (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with exacerbations of recurrent acute rhinosinusitis and either comorbid sarcoidosis 25 or ciliary dyskinesia 26 / cystic fibrosis were excluded due to possible variations in treatment and potential associations with BMI measures. Additional subjects were excluded if they had not yet entered the initial follow-up period (≤6-months) or were categorized as underweight with a BMI less than 18.5.…”
Section: Methodsmentioning
confidence: 99%